Khám phá các yếu tố ảnh hưởng tới thái độ học tập nội dung “Hình học” của học sinh trung học phổ thông tại Việt Nam - Lê Tuấn Anh, Lê Tuấn Anh; Nguyễn Huyền Trang Nguyễn Huyền Trang (Tạp chí Giáo dục, 2026)
Learning attitudes play a crucial role in determining students’ academic quality and performance. Previous studies have shown that students often encounter difficulties in learning Geometry; however, in Vietnam, there remains a lack of research focusing on students’ attitudes toward this subject. In response to this gap, the present study aims to identify the factors influencing high school students’ attitudes toward learning Geometry. Based on 22 observed variables and a five-point Likert scale, data were collected from 408 students across 12 high schools. The findings reveal three key factors affecting students’ learning attitudes: the perceived usefulness of Geometry, self-confidence in learning Geometry, and interest in learning Geometry. The results also indicate that students’ attitudes toward Geometry are not yet sufficiently positive across these three dimensions, thereby highlighting the need for appropriate pedagogical interventions to enhance students’ awareness, confidence, and interest in learning Geometry.